Methods and methods of teaching Russian language and literature - Sattarova Firuza Ulugbekovna; Gaybullaeva Zamira Turgunpulatovna; Bobazhanova Mavzhuda Toshpulatovna (Research Parks Publishing LLC, 2020)
This work is devoted to the study of the problem of the development and application of the most effective methodological techniques that promote the activation of the educational activities of students in the lessons of the Russian language. The following article looks into the ways to increase student enrollment in Russian language and literature classes.